Efek Potensial Moringa Oleifera pada Infeksi COVID-19 - Lusi Nursilawati Syamsi; Dian Ratih; Syamsudin Abidillah (Malahayati Nursing Journal, 2023)
ABSTRACT The COVID 19 pandemic is an outbreak caused by the coronavirus disease 2019 (COVID-19) with clinical manifestations of acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which has caused a large number of deaths worldwide. The most common complications of COVID-19 are cardiovascular and kidney disorders. The urgency to develop natural medicines with natural ingredients that are effective against COVID-19 is very important to maintain body immunity and at the same time protect the body from close contact with sufferers of COVID-19. Moringa plants have the potential to increase the body's resistance (immune booster) of sufferers against SARS-CoV-2. (COVID-19) and moringa plants have other health functions such as anti-inflammatory, antimicrobial, antidiabetic, antioxidant, antitumor, anticancer, antihypertensive, antiasthma, anticoagulation, antiurolithiasis, anthelmintic, antifertility, antihyperthyroid, and antialzheimer's. Several components of Moringa that play a role in the antiviral COVID-19 are Kaempferol, Pterygospermin, Morphine, Quercetin, and Apigenin-7-O-rutinoside. This Literature Review provides a basis for further research on the development of clinical applications of Moringa Oleifera for the treatment of SARS-CoV-2. Keywords: Covid-19, Potential Effects, Literature Review  ABSTRAK Pandemi COVID 19 adalah wabah yang disebabkan penyakit coronavirus 2019 (COVID-19) dengan manisfestasi klinis sindrom pernapasan akut coronavirus 2 (SARS-CoV-2) yang menyebabkan kematian yang cukup besar di seluruh dunia. Komplikasi tersering COVID-19 adalah gangguan kardiovaskular dan ginjal. Urgensi mengembangkan pengobatan natural bahan alam yang mempunyai efektivitas terhadap COVID 19 menjadi sangat penting untuk menjaga imunitas tubuh dan sekaligus menjaga tubuh terhadap kontak erat penderita COVID 19. Tanaman kelor mempunyai potensi meningkatkan daya tahan tubuh (booster imun )penderita terhadap penyakit SARS-CoV-2 (COVID 19) dan tanaman kelor memiliki fungsi Kesehatan lainnya seperti antiradang, antimikroba, antidiabetes, antioksidan, antitumor, antikanker, antihipertensi, antiasma, antikoagulasi, antiurolitiasis, anthelmintik, antifertilitas, antihipertiroid, dan antialzheimer. Beberapa komponen kelor yang berperan pada antivirus COVID-19 adalah Kaempferol, Pterygospermin, Morfin, Quercetin, dan Apigenin-7-O-rutinoside. Tinjauan Pustaka ini memberikan dasar untuk penelitian lebih lanjut pengembangan aplikasi klinis Moringa Oleifera untuk pengobatan SARS-CoV-2. Kata Kunci: Covid-19, Efek Potensial, Tinjauan Pustaka